Safety profile of lutein-based blue dyes and surgical lights - Romano, Mario R.; Conti, Federica; Lazzara, Francesca; Parolini, Barbara; Ferrara, Mariantonia; Bucolo, Claudio (Frontiers in Pharmacology, 2025)
IntroductionThe combination of surgical endoillumination and vital dyes has been associated with phototoxicity and retinal damage, despite vital dyes being mainly considered safe. Based on this perspective, the aim of the present study was to evaluate the effect of lutein-based blue dyes (LBBDs) on human retinal pigmented epithelial (ARPE-19) cells and their combination with surgical light exposure.MethodsARPE-19 cells were exposed to LBBDs and/or xenon/LED light according to the following experimental design: phase I, exposure to LBBDs only; phase II, exposure to lights only; phase III, single sequential exposure to LBBDs and xenon/LED light; and phase IV, double sequential exposure to LBBDs and xenon/LED light. ATPlite and reactive oxygen species (ROS) detection assays were used to assess the impact on cell viability and ROS production, respectively.ResultsNo cytotoxic effect was detected following the exposure to LBBDs for 5 min. LED and xenon lights elicited a cytotoxic effect and an overproduction of ROS for an exposure time of ≥5 min. The ROS overproduction following 5-min exposure of ARPE-19 cells to both LED and xenon lights was significantly (p < 0.05) counteracted by pre-treatment with LBBDs. Finally, after double sequential exposure to LBBDs and LED/xenon lights, 2% LBBD induced a significant (p < 0.05) reduction in ROS production compared to both LED/xenon exposure and 1% LBBD/light exposure.DiscussionThese findings demonstrated the primary role of light-induced damage as a primary contributing factor to potential retinal damage following peeling procedures. LBBDs provided a protective effect against light-induced oxidative damage, highlighting their potential role in enhancing the safety profile of staining in retinal surgery.